2008
DOI: 10.2341/07-77
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Erosive pH Cycling on Different Restorative Materials and on Enamel Restored with These Materials

Abstract: The different types of restorative materials tested were not able to protect adjacent enamel from erosion. Thus, the ability of a restorative material to prevent tooth erosion should not be considered when choosing a material. SUMMARYThis in vitro study evaluated the effect of erosive pH cycling on the percentage of surface microhardness change (%SMHC) and wear of different restorative materials and bovine enamel restored with these materials. Eighty enamel specimens were randomly divided into eight groups acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
81
0
26

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(110 citation statements)
references
References 29 publications
3
81
0
26
Order By: Relevance
“…4), the coating layer appeared to be fractured. Such voids and cracks have been attributed to the continuous internal acid-base reactions known for glass ionomers 38) ; and could also be due to the effect of the acidic environment on the integrity of material 39) . On the other hand, anti-caries effects of RMGIs were attributed to the presence of the loosely-bound fluoride ions from the glass fillers, which are free to move and protect enamel surface 15) .…”
Section: Discussionmentioning
confidence: 99%
“…4), the coating layer appeared to be fractured. Such voids and cracks have been attributed to the continuous internal acid-base reactions known for glass ionomers 38) ; and could also be due to the effect of the acidic environment on the integrity of material 39) . On the other hand, anti-caries effects of RMGIs were attributed to the presence of the loosely-bound fluoride ions from the glass fillers, which are free to move and protect enamel surface 15) .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that the erosive degradation of cements depends on the immersion time 18 , the type of beverage 12,14 and the acidity of the media 18 . It is known that during consumption, a beverage contacts the tooth surface and dental materials for only a short duration before it is washed away by saliva 19 .…”
Section: Discussionmentioning
confidence: 99%
“…The phosphoric acid found in the cola beverage could induce the softening of dimethacrylate and Bis-GMA polymers 14 and could favor the displacement of inorganic fillers, contributing to the formation of rough surfaces. This fact could also be associated with the decrease in VHN values found after erosive challenge for resin-based luting cements (Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations